2004
DOI: 10.1016/s0002-9440(10)63762-5
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes from Patients Lacking Collagen XVII Display a Migratory Phenotype

Abstract: Acquired or inherited junctional epidermolysis bullosa are skin diseases characterized by a separation between the epidermis and the dermis. In inherited nonlethal junctional epidermolysis bullosa, genetic analysis has identified mutations in the COL17A1 gene coding for the transmembrane collagen XVII whereas patients with acquired diseases have autoantibodies against this protein. This suggests that collagen XVII participates in the adhesion of basal keratinocytes to the extracellular matrix. To test this hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
109
1
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 49 publications
(67 reference statements)
6
109
1
7
Order By: Relevance
“…Previously, we showed that migrating keratinocytes cleave and leave the ectodomain of COL17 in the ECM as seen by the migration track in vitro, which was revealed by Ab HK139, which targets the N-terminal cleavage site at The present study also suggests the presence of binding proteins of cleaved COL17 ectodomain in the ECM, because IIF studies of cleavage-site-specific Abs on 1-M NaCl-split skin showed that the cleaved COL17 ectodomain remains on the epidermal side of artificial blisters. We and another group have reported that the C-terminus of COL17 binds with laminin 332 in vitro 23,29 . Because laminin 332 is always present on the dermal side of 1-M NaCl-split skin 3,30 , the present data indicate that another binding molecule, or molecules, on the epidermal side is present in the ECM, which binds with the shed COL17 ectodomain more strongly than laminin 332 does.…”
Section: Discussionmentioning
confidence: 90%
“…Previously, we showed that migrating keratinocytes cleave and leave the ectodomain of COL17 in the ECM as seen by the migration track in vitro, which was revealed by Ab HK139, which targets the N-terminal cleavage site at The present study also suggests the presence of binding proteins of cleaved COL17 ectodomain in the ECM, because IIF studies of cleavage-site-specific Abs on 1-M NaCl-split skin showed that the cleaved COL17 ectodomain remains on the epidermal side of artificial blisters. We and another group have reported that the C-terminus of COL17 binds with laminin 332 in vitro 23,29 . Because laminin 332 is always present on the dermal side of 1-M NaCl-split skin 3,30 , the present data indicate that another binding molecule, or molecules, on the epidermal side is present in the ECM, which binds with the shed COL17 ectodomain more strongly than laminin 332 does.…”
Section: Discussionmentioning
confidence: 90%
“…The overall structure of the ectodomain is that of a flexible rod (13,17). The intracellular ligands of collagen XVII include ␤ 4 -integrin, plectin, and BP230 in the hemidesmosomal plaque (4), and the extracellular ligands ␣ 6 -integrin and laminin 5 in the anchoring filaments (23,24). Further binding partners are likely to exist but still await identification.…”
Section: Biochemical Features and Ligand Interactions-collagenmentioning
confidence: 99%
“…This is supported by the finding that inhibition of collagen XVII processing preserved hemidesmosomal attachment in cultured keratinocytes (32). In the meantime it has become obvious that cell adhesion and motility involve a number of receptors and ligands depending on the spatial and temporal biological context (4) and that these processes are quite complex (24,27,33,34).…”
Section: Biochemical Features and Ligand Interactions-collagenmentioning
confidence: 99%
“…BP180 is suggested to be essential for correct organization of laminin 332 at the BL. This idea is based on the observation that the laminin 332-containing matrix in keratinocytes lacking BP180 is of poor quality (43).…”
Section: Discussionmentioning
confidence: 99%
“…Type I HDs are formed when BP230 is incorporated into the complex by binding to both ␤4 integrin and BP180. Both BP230 and plectin can bind to cytokeratins via interaction sites present in their respective COOH-termini (43), and ␣6␤4 integrin and BP180 have binding sites to the extracellular matrix (ECM) protein laminin 332. A, Calpain degrades the cytosolic domain of ␤4 integrin, forming 2 proteolytic fragments, which lack the binding sites for BP180 and BP230, thereby producing altered type I HDs.…”
Section: Discussionmentioning
confidence: 99%